"Cannot intubate, cannot oxygenate": A novel 2‐operator technique for cannula tracheotomy in an infant animal model—a feasibility study. Issue 12 (3rd October 2021) - Prunty, Sarah L.; Heard, Andrew M.; Chapman, Gordon; Challen, Andrew; Vijayasekaran, Shyan; von Ungern‐Sternberg, Britta S.
Abstract: Background: Evidence regarding optimal management of the "Cannot Intubate, Cannot Oxygenate" (CICO) scenario in infants is scarce. When inserting a transtracheal cannula for front of neck access direct aspiration to confirm intratracheal location is standard practice. This postmortem "infant airway" animal model study describes a novel technique for cannula tracheotomy. Aims: To compare a novel technique of cannula tracheotomy to an accepted technique to assess success and complication rates. Methods: Two experienced proceduralists repeatedly performed tracheotomy using an 18‐gauge BD InsyteTM cannula (BD, Franklin Lakes, NJ, USA) in 6 postmortem White New Zealand rabbits. Cannulas were attached either directly to a 5ml syringe (Direct Aspiration) or via a 25 cm length minimum volume extension tubing set (TUTA Healthcare Lidcombe, NSW, Australia) (Indirect Aspiration, 2 operator technique). Each technique was attempted a maximum of 12 times per rabbit with an ENT surgeon assessing success and complication rates endoscopically for each attempt. Results: 72 tracheotomy attempts were made in total, 36 for each technique. Initial aspiration through the needle was achieved in 93% (97.2% direct versus 89% indirect). Advancement of the cannula and continued aspiration (success) into the trachea occurred in 67% for direct compared with 64% for indirect aspiration. Direct aspiration was associated with higher rates of lateral (10.3% versus 5.6%) and posterior (19.4% versus 13.9%) wall injury compared with the indirect 2‐operator technique. Conclusion: Cannula tracheotomy in infant‐sized airways is technically difficult and seems frequently associated with tracheal wall injury. The reduced incidence of injury in the indirect group warrants further investigation in preclinical and clinical trials.